Pengaruh Penambahan Tepung Labu Kuning (Cucurbita moschata Durch) Terhadap Karakteristik Kulit Lumpia - Wijaya, Primena Sutra; Sugitha, I Made; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPADO - 10.24843/itepa.2025.v14.i01.p12, 2025)
Spring roll shells are generally made with wheat-based ingredients, where Indonesia must import wheat. The substitution of yellow pumpkin flour in food products can increase the ß-carotene content. This study aims to determine the effect of the addition of yellow pumpkin flour on the characteristics of spring roll skin and get the right ratio of wheat and yellow pumpkin flour to produce the best characteristics. This study used a Complete Random Design (RAL) with a comparative treatment of wheat flour and yellow pumpkin flour consisting of 5 levels, namely: 100%:0%, 90%:10%, 80%:20%, 70%:30% and 60%:40%. Each treatment was repeated 3 times, so that 15 experimental units were obtained. The data from the analysis results were tested statistically using Analysis of Variance (ANOVA) and treatments with real effects were further tested using the Duncan Multiple Range Test (DMRT). The results showed that the treatment of adding yellow pumpkin flour had a real effect on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, total ?-carotene, antioxidant activity, color intensity, scoring (color and texture), hedonic (color, aroma, taste, texture and overall acceptance), and ranking. The best treatment of spring roll skin in the P2 treatment (80% flour: 20% yellow pumpkin flour) produces a moisture content of 53.28%, ash content of 1.72%, protein content of 11.53%, fat content of 7.10%, carbohydrate content of 25.78%, crude fiber content of 5.96%, total ?-carotene 7.08 mg/100g, antioxidant activity 35.61%, color intensity L* 62.33, a* 10.67 and b* 47.00, sensory texture is a bit difficult to tear and liked,  the color is yellow and slightly liked, the aroma and taste are slightly liked, as well as the overall acceptance and ranking test are liked. Keywords: spring roll, yellow pumpkin. beta carotene